Primary or secondary wound healing of the pin sites after removal of the external fixator: A monocenter prospective randomized controlled trial. (1st June 2022) - Roth, F; Hoepelman, R; van de Wall, B; Cagienard, F; Babst, R; Beeres, F
Abstract: Objective: The aim of this monocentre randomized controlled trial was to compare primary wound closure using a single button suture to secondary wound healing of pin sites after removal of the external fixator. Methods: This non-inferiority trial included all patients who were treated with an external fixator. The primary outcome was infection. Secondary outcomes included all other complications, time to wound healing (in weeks), patients most satisfactory pin site, Visual Analogue Scale (VAS) for pain and the Vancouver Scar Scale (VSS) measured at every 2, 6, 12, 24 and 52 weeks. The most proximal pin site was randomly allocated (1:1) to either primary closure or secondary wound healing, while the following pin sites were treated alternately. Physicians at follow-up were blinded to the closure technique. Results: A total of 70 patient, providing 241 pin sites were included between 1st January 2019 and 1st March 2020. One-hundred-twenty-three pin sites were treated with primary closure and 118 with secondary wound healing. Median age was 55 (46–67), 44% was male and median duration of the external fixator was 6 days (4–8).There was no significant difference in pin site infections (2% in the primary closure group versus 0% in the secondary healing group). Wound healing was significantly faster in the primary closure group (median 2 vs. 6 weeks, p=0.013). Although not statistically significant, patients seemed more satisfied with the primary closed pin sites (55%). The Vancouver Scar scale showed no differences between groups. Conclusion: Primary closure of external pin sites does not result in higher infection rate than secondary wound healing and pin sites healed significantly faster after primary closure. Primary closure, therefore, should be the preferred method.